Investigation of horizontal and vertical distance of lithium-ion batteries on the thermal management of the battery pack filled with phase change material with the air flow - Zhang, Yuelei; Tavakoli, Farzan; Abidi, Awatef; Li, Z.; Aybar, Hikmet S.; Heidarshenas, Behzad (Elsevier, 2022)
Due to the importance of examining the temperature of battery packs (BYP), a study on the temperature of a lithium-ion BYP with 9 cylindrical cells is performed in this article. The BYP is filled with phase change material (PCM) to better temperature uniformity on the battery cells. The batteries and the PCM pack are placed in an air channel with two inlets. At the inlets, 4 arc blades are supposed to guide the airflow to enhance the uniformity of cooling in the BYP. By changing the horizontal and vertical distance (VD) of the batteries inside the pack, this study is carried out in 2500 s for the charging and discharging times of the batteries (1.5C rate). The thermal analysis is done on the batteries using COMSOL software. The results show that an increment in the horizontal distance (HD) of batteries has less effect on battery temperature (T-BT) and PCM phase change compared to their VD. By enhancing the horizontal and VDs of the batteries, the value of the PCM phase change during the maximum T-BT is higher. The heat transfer coefficient (HTCT) between the PCM and the air is also decreased by increasing the distance between the batteries. The T-BTs is not significantly impacted by changing the distance between them.
Keywords: Battery pack; Heat transfer; PCM; Temperature uniformity; Air-cooled